Policing corporate bribery: negotiated settlements and bundling - Hock, Branislav (Policing and society, 2021)
The rapid increase of negotiated out of court settlements in corporate crime cases has attracted significant academic attention. How the terms of settlements are constructed, however, remains under-studied. To address this gap, the paper observes that the terms of settlements often include a basket of allegations widely spread across time and geography. The paper conceptualises this as a form of ‘bundling’. The paper empirically explores the unique dynamics of corporate bribery cases that enable prosecutors to engage in bundling, and deconstructs bundling into two typologies (allegation bundling and enforcement bundling). From this perspective, this paper analyses official enforcement documentation relating to international bribery cases, supplemented with data from interviews with key informants who have experience of settlement negotiations in the US, the UK, and other countries. The analysis reveals that bundling provides efficiencies when resolving corporate crime cases, offers discounts to corporate defenders, and incentivizes coordinated multilateral enforcement. The practice of bundling allegations and enforcers confirms the character of negotiated settlements as a symbolic criminal law tool designed to reform the accused corporation through negotiation, persuasion and compliance.